KORELASI ANTARA PERHATIAN DAN MOTIVASI DARI ORANG TUA DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII MTsN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Yuni, Endang Srimah (STKIP PGRI Sumbar, 2014)
The attention and motivation from parent is a factor which is available in those individuals. Where have many factors which are influencing student Biology result, like attention and motivation. Based on observation which is done in MTsN Koto XI Tarusan Kabupaten Pesisir Selatan is gotten the information that in Biology, students have difficulties which comes from lack of interest, motivation, time management , and health, meanwhile from the students lack of parent attention, unsupported environment so that causing the student got lazy. So that directly or not, it will influence to students achievement. This research is aiming to know the relation of attention and motivation from parent with the result of student class VIII MTsN Tarusan Kabupaten Pesisir Selatan. The type of this research is descriptive. Population in this research is Student Class IX MTsN Koto XI tarusan Kabupaten Pesisir Selatan in 2014/2015 education year with total 197 students. Mean while the population which is being as sample are 47 people. This technique which is used in developing this sample is random sampling, where every member is taken randomly by looting. Based on the result in research which is gotten r 0,405 in attention of parent with enough interpretation, meanwhile value of r in motivation is 0,469 with enough interpretation. It can be conclude that there is correlation between attention and motivations from parent with the result of student in Class VIII MTsN Koto XI Tarusan Kabupaten Pesisir Selatan.